Pengaruh Dukungan Remote Audit terhadap Kualitas Audit melalui Teknologi Informasi di Era Teknologi 4.0 dan Masyarakat 5.0 - Nur Ismanidar; Muhammad Salman; Ahmad Ridha (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This paper aims to explore and conceptualize the influence of remote audit support on audit quality through information technology as an intervening variable in government financial oversight. The challenges of conducting audits due to the implementation of Large-Scale Social Restrictions (PSBB), followed by policy transitions that significantly restrict the movement and interaction among people, pose a unique challenge for auditors. Therefore, to maintain audit quality, remote audit support with the use of IT-Based as the basis for developing internal audit integration in the government is crucial in facilitating oversight. Utilizing information technology and establishing an early warning system, which is a shift from conventional to technology-based approaches, are preventive efforts in internal control through auditing, reviewing, evaluating, monitoring, and supervising other activities. The proposed method is a quantitative study that will involve auditors from the Supreme Audit Agency (BPKP). It is anticipated that this conceptual paper will provide valuable insights and information, paving the way for future empirical research in this field.